Effect of Collagen Concentration of Tilapia Fish Bones on The Quality of Skin Cream - Andre Wijaya; Junianto Junianto; Subiyanto Subiyanto; Rusky Intan Pratama (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Tilapia bone is a part of fishery waste that has not been utilized optimally and has low economic value. Utilization efforts can be made by utilizing the collagen content found in fish bones as a constituent material in the manufacture of skin creams. This study aims to determine the appropriate concentration of tilapia bone collagen to obtain the best physical and organoleptic characteristics. The research method used an experimental method consisting of 4 treatments, namely 0%, 5%, 10%, and 15%. Physical and organoleptic characteristics were tested using the F-test and Friedman's test, respectively, while the decision-making method used the Bayes method. Based on the results of the Bayes test, the addition of 10% tilapia bone collagen was the best treatment with a total value of 2.94. Physical characteristics at 10% collagen concentration have a pH value of 6.5, spreadability 3.76 cm, and humidity 80.8% according to cream quality standards, while the organoleptic characteristics of the cream have a homogeneous appearance, slightly yellowish white color, neutral aroma, and a soft semi-solid texture.